PENERAPAN TEKNOLOGI BLOCKCHAIN DALAM INDUSTRI KEUANGAN SYARIAH : TANTANGAN DAN PELUANG - Imam Kharits Najibulloh; Leny Rahmalia (J-EBI Jurnal Ekonomi dan Bisnis Islam, 2024)
The Islamic finance industry has experienced rapid growth in recent years. However, the industry still faces several challenges, such as lack of transparency, risk of fraud, and inefficiencies. Blockchain technology is emerging as a potential solution to overcome these challenges. Application of blockchain technology in the Islamic finance industry, including the challenges and opportunities obtained from its implementation. The research methodology involves a literature review and case study of various projects and pilot projects that use blockchain technology in the field of Islamic finance. In this research, the method used is a literature review. A literature review is carried out by collecting and analyzing various sources of information relevant to the research topic. The results of the literature review show that blockchain technology has great potential in overcoming the challenges of transparency, risk awareness and efficiency in the Islamic financial system. Case studies show examples of projects that integrate blockchain technology, such as a sharia interest rate platform, a price disclosure system, and a sharia digital payment solution. The analysis results show that the application of blockchain technology in the Islamic finance industry has the potential to reduce administrative costs, secure transactions, simplify transactions, and expand the Islamic investment market. However, there are still challenges that must be addressed, such as protocol standardization, regulations and current technological limitations. This research provides a basis for developing strategies for using blockchain technology that are more effective in supporting the growth of the Islamic finance industry.